The cutaneous beta human papillomavirus type 8 E6 protein induces CCL2 through the CEBPα/miR-203/p63 pathway to support an inflammatory microenvironment in epidermodysplasia verruciformis skin lesions - Vella, Luca; Sternjakob, Anna; Lohse, Stefan; Fingerle, Alina; Sperling, Tanya; Wickenhauser, Claudia; Stöckle, Michael; Vogt, Thomas; Roemer, Klaus; Ołdak, Monika; Smola, Sigrun (Frontiers in Cellular and Infection Microbiology, 2024)
Human papillomavirus type 8 (HPV8), a cutaneous genus beta HPV type, has co-carcinogenic potential at sun-exposed sites in patients suffering from the inherited skin disease epidermodysplasia verruciformis (EV). We had previously shown that Langerhans cells responsible for epithelial immunosurveillance were strongly reduced at infected sites and that the HPV8 E7 protein interferes with the CCAAT/enhancer-binding protein (C/EBP)β to suppress the Langerhans cell chemokine CCL20. At the same time, however, we observed that EV lesions are heavily infiltrated with inflammatory immune cells, which is similar to the situation in HPV8 E6 transgenic mice. To identify critical inflammatory factors, we used a broad multiplex approach and found that the monocyte attracting chemokine CCL2 was significantly and strongly induced by HPV8 E6 but not E7-expressing HaCaT cells, which were used as a model for UV-damaged skin keratinocytes. Conditioned media from HPV8 E6-expressing keratinocytes enhanced CCL2-receptor (CCR2)-dependent monocyte recruitment in vitro, and macrophages predominated in the stroma but were also detected in the epidermal compartment of EV lesions in vivo. CCL2 induction by HPV8 E6 was even stronger than stimulation with the proinflammatory cytokine TNF-α, and both HPV8 E6 and TNF-α resulted in substantial suppression of the transcription factor C/EBPα. Using RNAi-mediated knockdown and overexpression approaches, we demonstrated a mechanistic role of the recently identified C/EBPα/miR-203/p63 pathway for HPV8 E6-mediated CCL2 induction at protein and transcriptional levels. Epithelial co-expression of p63 and CCL2 was confirmed in HPV8 E6-expressing organotypic air–liquid interface cultures and in lesional EV epidermis in vivo. In summary, our data demonstrate that HPV8 oncoproteins actively deregulate epidermal immune homeostasis through modulation of C/EBP factor-dependent pathways. While HPV8 E7 suppresses immunosurveillance required for viral persistence, the present study provides evidence that E6 involves the stemness-promoting factor p63 to support an inflammatory microenvironment that may fuel carcinogenesis in EV lesions.